2021
DOI: 10.3390/ijerph18063091
|View full text |Cite
|
Sign up to set email alerts
|

Social-Emotional Learning Competencies and Problematic Internet Use among Chinese Adolescents: A Structural Equation Modeling Analysis

Abstract: To advance the understanding about social-cognitive factors related to Chinese adolescents’ experience with problematic Internet use (PIU), we examined the associations between social-emotional learning (SEL) competencies (i.e., responsible decision-making, social awareness, self-management, self-awareness, and social relationship) and problematic Internet use (PIU) among 1141 11th grade high school students from Southwest China. Through comparing the latent means of PIU across students with different demograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 80 publications
(80 reference statements)
1
10
0
1
Order By: Relevance
“…Thus, these two scales’ latent means of teachers’ perception of the three types of school-wide practices and school-wide bullying cannot be compared. The lack of intercept-level measurement invariance of the DDTS-T and SWBS found in the present study was consistent with previous studies, in which factors contributing to the cross-country differences of school disciplinary and SEL practices and the bullying phenomenon were discussed (Bear et al, 2016; Chen et al, 2021). For example, researchers found that punitive practices, such as school removals, were less common in China than in the United States because it is inconsistent with the cultural value of social harmony and self-discipline that is highly prized in the Chinese culture, consistent with the Confucian value (Crystal et al, 1994; Hui et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, these two scales’ latent means of teachers’ perception of the three types of school-wide practices and school-wide bullying cannot be compared. The lack of intercept-level measurement invariance of the DDTS-T and SWBS found in the present study was consistent with previous studies, in which factors contributing to the cross-country differences of school disciplinary and SEL practices and the bullying phenomenon were discussed (Bear et al, 2016; Chen et al, 2021). For example, researchers found that punitive practices, such as school removals, were less common in China than in the United States because it is inconsistent with the cultural value of social harmony and self-discipline that is highly prized in the Chinese culture, consistent with the Confucian value (Crystal et al, 1994; Hui et al, 2011).…”
Section: Discussionsupporting
confidence: 93%
“…Although researchers and policymakers have recognized the school-wide Positive Behavioral Intervention Support (PBIS) programs and social and emotional learning (SEL) programs as promising school-wide practices to prevent and reduce bullying in the United States and some other Western countries in the past decade (Good et al, 2011; Smith & Low, 2013), we have a minimal understanding of how the critical factors related to these commonly used school-wide practices universally and uniquely influence bullying prevention outcomes in schools beyond North America and the larger global context. Such cross-country understanding is essential for developing and adapting effective evidence-based school-wide bullying prevention practices and programs across different cultural contexts and school systems in different countries, especially considering that cross-country differences in school-wide practices and bullying phenomenon have been evidenced in the research literature (Bear et al, 2016; Chen et al, 2021).…”
Section: School-wide Practices and Bullying Preventionmentioning
confidence: 99%
“…However, although previous studies showed that school climate played an important role in Chinese adolescents' behaviors (e.g., Bear et al, 2018; Li et al, 2016; Nie et al, 2018), few studies have investigated the mechanisms underlying the relationship between perceived school climate and adolescent behavioral outcomes, particularly in Chinese culture context. While, social‐emotional learning (SEL) is regarded as general psychosocial competence in positive youth development (PYD) that is applicable across contexts and developmental stages (Shek et al, 2019; Tolan et al, 2016), and it has attracted great interest in the education systems in Western societies (Chen et al, 2021; Wu et al, 2016). However, SEL competencies are generally not valued in schools in mainland China due to the morbid emphasis on academic excellence.…”
Section: Introductionmentioning
confidence: 99%
“…The findings from previous studies suggest a relationship between socio-emotional skills and problematic Internet use [ 36 ]. Self-control, impulsivity, and social skills were among the cognitive factors that predicted problematic Internet use and fit the concept of socio-emotional competences.…”
Section: Introductionmentioning
confidence: 99%
“…Self-control, impulsivity, and social skills were among the cognitive factors that predicted problematic Internet use and fit the concept of socio-emotional competences. Chen et al found that overall socio-emotional competencies have a significantly negative association with students’ problematic Internet use [ 36 ]. The findings from previous studies also suggest a relationship between socio-emotional skills and cyberbullying.…”
Section: Introductionmentioning
confidence: 99%